Schwannoma of Gingiva: A Rare Case Report - Purwar, Parth; Dixit, Jaya; Singhal, Divya; Bhartiya, Kishlay; Vashistha, Madhukar; Singh, Manish (Journal of Orofacial Research, 2014)
The ‘schwannoma’, an infrequently occurring benign neural tumor, does not demonstrate proclivity for intraoral locations. However, if present the gingiva is only sporadically involved. In this case report, we present a unique case of 17-year-old female patient with enlarged nodular firm gingival mass in relation to hermandibular anterior teeth which was provisionally diagnosed as pyogenic granuloma. However, the histologic as well as immunohistochemical findings revealed it to be characteristic of schwannoma. After appropriate management, the patient has been kept under stringent follow-up and no recurrence Schwannoma, Pyogenic granuloma, Immunohistochemistry, Gingiva, Excisionhas been noted.